Original equipment manufacturers, Inc. a methods study - Apostol, Arnold Cecilio; Bolanos, Rolando; Bucaycay, Jocelyn; Gonzales, Imelda; Hamada, Melody; Ledesma, Raymond (College of Engineering, 1989)
The group hopes to improve productivity of the study by reducing the work content. Wasted effort is reduced by integrating activities-in the base assembly, the circuitous transport and operation activities of going to the cutter and back is totally eliminated by cutting beforehand ashlars into specific sizes and having a well planned design of where each ashler will be placed. Another is by doing away with repetitive activities-in the screw and collar sub-assembly, we propose marking everything before cutting. Time delay was minimized by devicing jigs and trays. When we attached sides of the table top it usually takes at least two hours to complete one. In using the suggested trays, there is virtually no time delay since drying time is not a factor to consider. Easy accessibility of machines such as the drill press being relocated to the center of the woodworks and sheetworks provide lesser transport time. Details of the above are discussed in the succeeding sections.